Diagnostic performance of 18fluorodesoxyglucose positron emission/computed tomography and magnetic resonance imaging in detecting T1‐T2 head and neck squamous cell carcinoma. (10th June 2017) - Chaput, Anne; Robin, Philippe; Podeur, Fabien; Ollivier, Morgan; Keromnes, Nathalie; Tissot, Valentin; Nonent, Michel; Salaün, Pierre‐Yves; Rousset, Jean; Abgral, Ronan
Abstract : Objectives/Hypothesis: The aim of this study was to assess and compare the diagnostic accuracy of 18 fluorodesoxyglucose positron emission/computed tomography (FDG‐PET/CT) and magnetic resonance imaging (MRI) to detect T1‐T2 head and neck squamous cell carcinoma (HNSCC). Study Design: Prospective case series. Methods: Thirty‐five consecutive patients with histologically proven T1‐T2 HNSCC were prospectively included. All patients underwent pretherapeutic FDG‐PET/CT and MRI. Two nuclear medicine physicians and 2 radiologists blindly reviewed all FDG‐PET/CT and MRI, respectively. A five‐point qualitative scale was used to estimate tumor detection ability. Sensitivity of each modality was compared together using a McNemar test. Interobserver variability was assessed by kappa index (κ) of Cohen statistics. Maximal standardized uptake value (SUVMAX ), metabolic tumor volume (MTV) in FDG‐PET/CT, and gadolinium enhancement (%GE) in MRI of each tumor were recorded and compared with T stage using a Mann‐Whitney test. Tumor‐to‐normal tissue ratios in FDG‐PET/CT and MRI (TNRPET and TNRMRI ) were calculated and compared together using a Student t test. Results: Among the 35 primary tumors, 29 were detected by FDG‐PET/CT and 22 by MRI. MRI detected none of the six lesions incorrectly identified by FDG‐PET/CT. FDG‐PET/CT correctly identified seven of the 13 MRI false‐negative results. Sensitivity of FDG‐PET/CT to detect T1‐T2 HNSCC was significantly higher than MRI (83% vs. 63%, P = .015). T stage was significantly correlated with MTV ( P = .002) unlike with SUVMAX ( P = .06) and %GE ( P = .70). TNRPET was significantly higher than TNRMRI (3.5 ± 3.2 vs. 1.2 ± 0.3, P < .0001). Conclusions: Our study showed a higher diagnostic accuracy of FDG‐PET/CT than MRI to detect T1‐T2 HNSCC with a good interobserver agreement. Level of Evidence: 4. Laryngoscope, 128:378–385, 2018